CCSP Certified Cloud Security Professional practice exams - Carter, Daniel, CISSP (McGraw Hill Education, 2018)
Don't Let the Real Test Be Your First Test! This highly effective self-study guide covers all six domains of the challenging Certified Cloud Security Professional exam as well as the CCSP Common Body of Knowledge, developed by the International Information Systems Security Certification Consortium (ISC)2®. To reinforce important skills and facilitate retention, every question is accompanied by in-depth explanations for both correct and incorrect answers. Designed to help you pass the test with ease, this book is also an ideal companion to the bestselling CCSP® Certified Cloud Security Professional All-in-One Exam Guide . Covers all six exam domains: " rchitectural Concepts and Design Requirements " loud Data Security " loud Platform and Infrastructure Security " loud Application Security " perations " egal and Compliance CD ICON Electronic content includes: " 50 practice questions " ecured book PDF